Analysis and optimization of open micro-channel heat sink with pin Fins by modified grey relational optimization - Raza, Syed Shamim; Bhushan, Ravi (The Nucleus, 2024)
This work successfully utilized grey relational optimization in conjunction with the standard deviation objective weighting approach to improve various response parameters in a microchannel heat sink with pin fins, including: the surface Nusselt number and total surface heat flux. Six process parameters were chosen for the simulation research of the open microchannel heat sink with pin fins based on the L-27 orthogonal array. These parameters are heat sink length (L), heat sink width (W), number of fins (N), fin height (a), base height (b) and fin thickness (d). The surface Nusselt number and total surface heat flux were selected as the output parameters. This work aids in understanding the effect of various parameters on the open microchannel heat sink with pin fins. The standard deviation objective weighting - grey relational optimization method optimized the process parameters. ANSYS Fluent software was utilized to simulate the entire open microchannel heat sink with pin fins according to the L-27 orthogonal array. The optimal configuration for the process parameters was determined to be a heat sink length of 80 mm, width of 100 mm, 5 fins, fin height of 30 mm, base height of 8 mm and fin thickness of 2 mm. Among these parameters, the number of fins was found to be the most influential factor, followed by base height, fin thickness, width of the heat sink, fin height, and length of the heat sink. The findings indicate that these parameters play a critical role in the thermal performance optimization of microchannel heat sinks.